Are foraminal stenosis severity and herniation level associated with the treatment success of cervical interlaminar epidural steroid injection? - (:unkn) unknown (American Society of Interventional Pain Physicians, 2020)
Background: Foraminal stenosis, defined as a narrowing of the cervical neural foramen, is one of the most common causes of upper extremity radicular pain. Objectives: The aim of our study was to determine the effects of the severity of neural foraminal stenosis and spinal herniation level on treatment success in patients treated with interlaminar epidural steroid injections (ILESI) due to cervical disc herniation-related radiculopathy and their possible predictive roles. Study Design: A retrospective assessment. Setting: A university hospital interventional pain management center. Methods: We performed our study between August 2017 and February 2019, retrospectively. All patients’ demographic characteristics, clinical and demographic data, including pain scores before and after cervical ILESI in the first hour, third week, and third month follow-ups, presence of motor deficits, symptom side, symptom duration before cervical ILESI, and whether there was progression to surgery in the 3-month period after injection, were collected. Results: We evaluated 61 patients in the final analysis. When the spinal herniation levels and foraminal stenosis grades were compared, there was a significant difference between the groups (P = 0.003, P = 0.005). We reported significant correlations between foraminal stenosis grade (odds ratio [OR], –0.425, P = 0.038) and spinal herniation level (OR, –0.925, P = 0.001) and treatment success. Limitations: Our study’s design was retrospective. Conclusions: Cervical ILESI is a reliable treatment option that provides a significant reduction in pain of patients with cervical radiculopathy. However, the success of ILESI treatment may be negatively affected in these patients in the presence of high spinal level cervical disc herniation and severe foraminal stenosis. Therefore considering these 2 parameters in predicting the patient population who will benefit from cervical ILESI is of importance in terms of decreasing potential complications. © 2020, American Society of Interventional Pain Physicians. All rights reserved.
Keywords: Cervical disc herniation; Foraminal stenosis; Interlaminar epidural steroid injections; Radicular pain; Spinal level